Effect of packing materials and storage period on germination and seedling growth of mustard (Brassica juncea) - BHADAURIA, H S; SOLANKI, S S; PATEL, B K; PATHAK, H C (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 2004–09 to study the storability of Indian mustard (Brassica juncea L. Czern & Coss.) seed to prolong seed viability and seedling vigoyur index. Seeds of mustard varieties, ‘GM 1’ and ‘GM 2’ produced during winter (rabi) season 2003–04 were stored in six different packing materials, ie seed packed in polyethylene bag, seeds packed in cloth bag, seed packed in paper bag, seed kept in iron bin, seed kept in iron bin and sealed with cellophane tape and seed kept in iron bin with 1% CaCl2 and sealed with cellophane tape. Seed germination percentage, root length, shoot length and seedling vigour were studied. In the fifth year the highest mean values of germination percentage (60.40), root length (8.55 cm), shoot length (6.09 cm) and seedling vigour index (966.85) were recorded in seed stored in iron bin with CaCl2 (1%) and sealed with cellophane tape (P6), followed by seed packed in polyethylene bag (P1). The Indian mustard variety ‘GM 1’ exhibited better storability capability than ‘GM 2’.